ASYMPTHOTIC BEHAVIOR OF MAGNETO-ELASTIC WAVES IN A CONDUCTIVE BOUNDED ENVIRONMENT - Santiago Ayala, Yolanda Silvia (2008)
Using semigroup theory we are going to prooue the global existence solution o] a evolution model, which represente the magneto-elastic waves in a boundary conduciive media. Also, we are going to prooue that the the system is well set and using Dinamic Systems and La Salle 's Invariance Principie we are going to show that the energy asociated to the system decays to zero when t→+ ∞.